2018
DOI: 10.1166/jbn.2018.2584
|View full text |Cite
|
Sign up to set email alerts
|

Tea Polyphenols Functionalized and Reduced Graphene Oxide-ZnO Composites for Selective Pb2+ Removal and Enhanced Antibacterial Activity

Abstract: New materials with good purification of water quality (heavy metal ions removal and inhibition of bacteria) have increasingly attracted more research attentions. Considering the advantages of zinc oxide (ZnO) and tea polyphenol functionalized and reduced graphene oxide (TPG), the TPG-ZnO composites were prepared under moderate hydrothermal method and characterized by various methods. Lead ions (Pb2+) and Streptococcus mutans (S. mutans) were used to evaluate the adsorption capacity and antimicrobial activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Zheng et al designed nanocomposites by fabrication of zinc oxide with tea polyphenol with reduced graphene oxide (TPG-ZnO). Designed material was applied for the removal of heavy metal ions with an added advantage of antibacterial properties [143]. They applied this material for the removal of Pb 2+ ions from aqueous solution with adsorption efficiency of 98.9%, and the adsorbent was found to possess antibacterial properties against Streptococcus mutans with 99% eradication [143].…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al designed nanocomposites by fabrication of zinc oxide with tea polyphenol with reduced graphene oxide (TPG-ZnO). Designed material was applied for the removal of heavy metal ions with an added advantage of antibacterial properties [143]. They applied this material for the removal of Pb 2+ ions from aqueous solution with adsorption efficiency of 98.9%, and the adsorbent was found to possess antibacterial properties against Streptococcus mutans with 99% eradication [143].…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…Designed material was applied for the removal of heavy metal ions with an added advantage of antibacterial properties [143]. They applied this material for the removal of Pb 2+ ions from aqueous solution with adsorption efficiency of 98.9%, and the adsorbent was found to possess antibacterial properties against Streptococcus mutans with 99% eradication [143]. Mousavi et al designed nanocomposites of graphene oxide with iron oxide magnetite nanoparticles Fe 3 O 4 and applied them for the removal of Pb 2+ ions from water and the material showed 98% removal efficiency with a capacity of 126.6 mg/g [144].…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…Different carbonaceous materials have been used for the removal of heavy metals, namely single-wall carbon nanotubes (SWCNTs), functionalized-SWCNTs, multiwall carbon nanotubes (MWCNTs), functionalized-MWCNTs, graphene and graphene oxide, etc. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. A comprehensive review was recently published on the application of carbon nanomaterials in water treatment and environmental remediation [14].…”
Section: Comparison Of Pks-derived Activated Carbon Materials With Other Carbonaceous Materialsmentioning
confidence: 99%
“…Graphene is a type of classical two-dimensional nanomaterial with good biocompatibility and electrical conductivity [ 39 ]. The excellent biocompatibility of RGO nanomaterials and its better electrical conductivity than graphene and graphene oxide were verified by a variety of studies [ 40 , 41 ]. 1% (W/WPCL) RGO and 1% (W/WPCL) MLT has respectively reported that have less cytotoxicity and could promote cell adhesion and proliferation on PCL scaffolds [ 20 , 29 ].…”
Section: Discussionmentioning
confidence: 99%